Development of regional reliability hurdle rate for South Africa - Van Harte, MA (Department of Electrical Engineering, 2014)
The reform of the electricity distribution industry has resulted in the national regulator authorities moving from Rate of Return (ROR) to Incentive Based Regulation (IBR) quality regulation mechanism. This has influenced the reporting, planning, design, operating and maintenance (O&M) philosophy surrounding distribution networks and service delivery to the end customer. The introduction of IBR regulation has created a need to understand how the IBR scheme implemented will influence the capital and operating investment decisions. The aim of the work leading up to this thesis has been to develop reliability hurdle rates that include the effect of the IBR scheme implemented by the national regulator authority of South Africa. This will enable the network planner to compare the investment decision with the reward / penalty scheme. The thesis addresses the challenges facing distribution network planning to achieve the appropriate (optimal) balance of investment cost vs. reliability levels. Value Based Reliability Planning (VBRP) methodology is an approach to evaluate capital investment decisions by quantifying, in economic terms, the benefits of improving reliability (System Average Interruption Duration Index (SAIDI) per capital cost required) by comparing different reliability improvement alternatives. This is achieved by relating the investment decision to the reward / penalty scheme introduced by National Electricity Regulator for South Africa (NERSA). To reach this goal this thesis derived a reliability hurdle rate by utilising benefit-to-cost analysis principles by considering the shape of the reward / penalty scheme. Furthermore, this necessitates the determination of the optimal balance between investment decisions to obtain improvement in the continuity of supply indices. One of the fundamental objectives is therefore to relate the IBR and VBRP in an efficient and effective way, that is the aim of the national regulator authority. A new method to determine a regional and national reliability hurdle rate is proposed by the thesis. This is a first step in obtaining an optimal expansion alternative and allows the planner to compare the preferred alternative selected against a hurdle rate. Since the method considers the reward / penalty scheme, the thesis first reviews the principles that influence the quality regulation mechanisms and the benefit-to-cost analysis techniques. The second step demonstrates the derivation of the reliability hurdle rate utilising the reward / penalty scheme adopted within South Africa. Parameters considered include the number of customers and the interruption indices in each region. The application studies demonstrate the derivation of the regional reliability hurdle rate from the six regions within South Africa. This allows the derivation of regional reliability hurdle rate from the different regional reward / penalty schemes. Finally, a sensitivity analysis is performed to understand the influence of different parameters, which will influence the regional reliability hurdle rate. The results from the case studies show that, when NERSA creates the reward / penalty scheme, it is crucial that the approved method is applied to determine the shape of the scheme implemented, which will allow the derivation of the reliability hurdle rate. The new method is suitable for implementation where the IBR quality regulation mechanism has been adopted by the national electricity authorities. Furthermore, the reliability hurdle rate derived can be used to compare the investment decision against the improvement required in the continuity of supply indices. This ensures the trade-off between the expansion investment and improvement in the reliability levels